A Novel Wideband Circularly Polarized Antenna for RF Energy Harvesting in Wireless Sensor Nodes - Nhu Huan Nguyen; Thi Duyen Bui; Anh Dung Le; Anh Duc Pham; Thanh Tung Nguyen; Quoc Cuong Nguyen; Minh Thuy Le (International Journal of Antennas and Propagation)
A novel wideband circularly polarized antenna array using sequential rotation feeding network is presented in this paper. The proposed antenna array has a relative bandwidth of 38.7% at frequencies from 5.05 GHz to 7.45 GHz with a highest gain of 12 dBi at 6 GHz. A corresponding left-handed metamaterial is designed in order to increase antenna gain without significantly affecting its polarization characteristics. The wideband circularly polarized antenna with 2.4 GHz of bandwidth is a promising solution for wireless communication system such as tracking or wireless energy harvesting from Wi-Fi signal based on IEEE 802.11ac standard or future 5G cellular. A potential application of this antenna as a receiving antenna for RF-DC device to obtain DC power for a wireless sensor node from Wi-Fi signal is shown.